2023
DOI: 10.1038/s41536-023-00276-5
|View full text |Cite
|
Sign up to set email alerts
|

PDGF inhibits BMP2-induced bone healing

Abstract: Bone regeneration depends on a pool of bone/cartilage stem/progenitor cells and signaling mechanisms regulating their differentiation. Using in vitro approach, we have shown that PDGF signaling through PDGFRβ inhibits BMP2-induced osteogenesis, and significantly attenuates expression of BMP2 target genes. We evaluated outcomes of treatment with two anabolic agents, PDGF and BMP2 using different bone healing models. Targeted deletion of PDGFRβ in αSMA osteoprogenitors, led to increased callus bone mass, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…They also observed antagonistic effects between the signaling of these two proteins when administered simultaneously [ 69 ]. Another study by Novak et al (2023) showed that the combination of these two growth factors compromises the bone healing model, with PDGF-BB inhibiting BMP-2-induced osteogenesis [ 70 ]. This effect could be associated with PDGF-BB’s inhibition of the BMP2/Smad canonical signaling pathway [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also observed antagonistic effects between the signaling of these two proteins when administered simultaneously [ 69 ]. Another study by Novak et al (2023) showed that the combination of these two growth factors compromises the bone healing model, with PDGF-BB inhibiting BMP-2-induced osteogenesis [ 70 ]. This effect could be associated with PDGF-BB’s inhibition of the BMP2/Smad canonical signaling pathway [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we did not observe significant deletion of Dll4 in Cdh5CreER/DllD female mice. We previously reported lower efficiency of Cre recombination in female animals using the aSMA promoter (22,23,48). Sex differences and/or decreased targeted gene expression in females could lead to inefficient Cre recombination (23).…”
Section: The Decision Of Common Lymphoid Progenitors To Differentiate...mentioning
confidence: 99%
“…Critical size femoral defects. C57Bl/6J animals aged 3.5-7 months were used to evaluate critical size femoral healing (2 mm) using an established protocol and commercially available external fixation (MouseExFix, RISystem) (48). DLL4 (5 µg, R&D Systems, USA), JAG1 (6 µg, R&D Systems, USA), or their combination with BMP2 (5 µg) was applied on an adsorbable collagen sponge as a scaffold (Medtronic, USA) cut to size (3 × 4 × 4 mm) onto which growth factors were loaded in a 7 µl volume.…”
Section: Sex As a Biological Variablementioning
confidence: 99%
See 1 more Smart Citation
“…BMP2 is a highly conserved functional protein of the TGF-β family, promoting osteogenesis ( 52 , 53 ). It was shown by immunofluorescence that XBP1 highly expresses in human periodontal ligament cells (hPDLCs).…”
Section: Regulation Of Xbp1 In Osteoblast Differentiationmentioning
confidence: 99%